Strategi pemasaran dalam Desain Interior dan Tren Kontemporer: Model Bisnis Terkini: (Studi Pada Inhiven Desaign Sidoarjo) - Sholeh, Isa Mansyur (FEB Universitas Maritim Semarang, 2024)
Inhiven Design is a company that combines graphic design with interior design to provide creative and integrated solutions in various fields such as housing, offices, and commercial. The author's purpose in conducting this study is to analyze the history of the early formation of Inhiven Design? Then what are the problems faced during the establishment of Inhiven Design? And how does Inhiven Design optimize sales in its marketing? The method used in this study is qualitative observation with primary data collection through direct interviews. This study examines the development of Inhiven Design, including the company profile, history of its establishment, and marketing and management strategies implemented. Data were collected through qualitative observation and direct interviews with team members to understand the marketing strategy carried out by Inhiven Design by applying contemporary trends in interior design. The results of the analysis show that the success of Inhiven Design depends not only on technical skills and creativity, but also on the ability to adapt to market changes and maintain good relationships with customers and business partners.